Building an Articulate and Collective Resistance to Surveillance Technologies in Brazil - Bell, Kainen; Lima, Thallita G. L. (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
Facial recognition technologies (FRTs) have rapidly expanded as instruments of algorithmic governance, reorganizing regimes of visibility, classification, and control. In Brazil, their diffusion intersects with long-standing racialized forms of urban management, disproportionately targeting Black and peripheral communities under the narrative of enhanced public security. Rather than being supported by evidence of effectiveness, these deployments are driven by techno-solutionist imaginaries that frame technological innovation as the preferred response to structural social issues, enabling experimental systems to circulate with limited legal, social, or technopolitical safeguards. This article examines how Brazilian grassroots organizations and civil society coalitions mobilize to contest this expansion through counter-surveillance practices, legal and policy challenges, public advocacy, and data activism. Drawing on ethnographic and qualitative research, including sustained engagement with the national campaign Tire Meu Rosto Da Sua Mira, the analysis situates these practices within debates in surveillance studies, science and technology studies (STS), and critical race and feminist approaches to technology. The article argues that resisting FRTs requires not only exposing technical failures but also reshaping the sociotechnical imaginaries that render these systems legitimate. By foregrounding situated resistance emerging at the intersection of racial justice, urban inequality, and data activism, the study shows how these actors contest the normalization of biometric surveillance and articulate alternative, more democratic visions of public security.